2023
DOI: 10.1002/adfm.202211830
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Small Cations on the Electroluminescence Performance of Perovskite Light‐Emitting Diodes

Abstract: The delicate engineering of monovalent cations in perovskite material has led to continuous performance breakthroughs and stability improvement for the perovskite light‐emitting diodes (PeLEDs). However, the exact role of A‐site cations on the electroluminescence (EL) performance and degradation mechanism of PeLEDs has not been systematically answered yet. Herein, it is demonstrated that the most commonly used methylammonium cation (MA+) has an adverse effect on the electrochemical reaction at the interface be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…FA + and Cs + are the two other most popular A-site cations in MHPs. The migration of the two cations has also been reported in the literature. , Nagi et al utilized ToF-SIMS depth analysis and observed that FA + accumulated at the Au/MoO 3 interface in degraded FA-based PeLEDs, which could be a major contributor to the short operational lifetime . Pavlovetc et al reported bias-induced migration of both FA + and Cs + in mixed-cation perovskite lateral devices.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…FA + and Cs + are the two other most popular A-site cations in MHPs. The migration of the two cations has also been reported in the literature. , Nagi et al utilized ToF-SIMS depth analysis and observed that FA + accumulated at the Au/MoO 3 interface in degraded FA-based PeLEDs, which could be a major contributor to the short operational lifetime . Pavlovetc et al reported bias-induced migration of both FA + and Cs + in mixed-cation perovskite lateral devices.…”
mentioning
confidence: 81%
“…Additionally, Nagi et al reported that the incorporation of Cs + cations (with a Cs/Pb molar ratio of 0.15) in the FA-PeLEDs significantly suppressed the ion migration process and enhanced the device stability. This led to a smaller efficiency roll-off and an elongated operational half-lifetime of 190.1 h under a current density of 20 mA/cm 2 , while the FAPbI 3 device exhibited an operational half-lifetime of 38.4 h under the same testing conditions . Adverse impacts on device stability would occur with an increased doping ratio of Cs + .…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[12][13][14][15][16] However, the PeLEDs suffer from serious ion migration issue under electric field, resulting in electrochemical reaction between adjacent layers and perovskite decomposition. [17,18] Bulky organic cations with various geometries have been introduced into 3D perovskites to form quasi-two-dimensional (quasi-2D) perovskites, consisting of alternative inorganic and organic layers, which aims to increase the ion migration barrier and suppress the decomposition process. [19][20][21] The quasi-2D perovskite films typically consist of quasi-2D phases with a series of different inorganic layers and also some 3D phases.…”
Section: Introductionmentioning
confidence: 99%